Go Deeper, Go Deeper: Understanding submarine command and control during the completion of dived tracking operations. (May 2018) - Roberts, Aaron P.J.; Stanton, Neville A.; Fay, Daniel T.
Abstract: This is a world's first-of-a-kind study providing empirical evidence for understanding submarine control room performance when completing higher and lower demand Dived Tracking (DT) scenarios. A submarine control room simulator was built, using a non-commercial version of Dangerous Waters as the simulation engine. The creation of networked workstations allowed a team of nine operators to perform tasks completed by submarine command teams during DT. The Event Analysis of Systemic Teamwork (EAST) method was used to model the social, task and information networks and describe command team performance. Ten teams were recruited for the study, affording statistical comparisons of how command team roles and level of demand affected performance. Results indicate that command teams can covertly DT a contact differently depending on demand (e.g. volume of contacts). In low demand it was possible to use periscope more often than in high demand, in a 'duck-and-run' fashion. Therefore, the type of information and frequency of particular task completion, was significantly different between the higher and lower demand conditions. This resulted in different operators in the command team experiencing greater demand depending on how the DT mission objective was completed. Potential bottlenecks in the command team were identified and implications are discussed alongside suggestions for future work. Highlights: In complex sociotechnical systems control room configuration impacts upon information flow. Operational demand significantly affected information exchange. Command team strategy is highly dependent on operational demand. Co-location of operators and interface information has the potential to maximise efficiency.